A poorly soluble organic electrode material for high energy density lithium primary batteries based on a multi-electron reduction. Issue 82 (30th September 2021) - Chen, Zifeng; Sun, Pengfei; Bai, Panxing; Su, Hai; Yang, Jixing; Liu, Yang; Xu, Yunhua; Geng, Yanhou
Abstract : A poorly soluble and high energy density organic compound is reported for lithium battery cathode materials, delivering a high energy density of 1392 W h kg −1 . This work provides a strategy for realizing high energy density lithium–organic batteries. Abstract : Here we report an organic cathode material with poor solubility for lithium primary batteries, i.e. indeno[3, 2- b ]fluorene-6, 12-dione. Each carbonyl group experiences a four-electron reduction to a methylene group, resulting in a high energy density of 1392 W h kg −1, which is among the best results for organic electrode materials.